Alternative (non-military) service in Estonia: experience for improving Ukraine’s national security - Y.M. Kotylko (Економіка, управління та адміністрування)
The article provides a comprehensive analysis of the system of alternative (non-military) service in Estonia as an integral part of the broad-based national defense concept and a tool for strengthening societal resilience to crises. The relevance of the topic is driven by the growing role of non-military security components in the context of modern threats, as evidenced by Estonia’s experience in preparing and utilizing alternative service resources to support public security and civil protection.